The biopsychosociospiritual perception of the process of finitude in the triad Nurse X Patient X Family (Research, Society and Development, 2020)
According to the WHO, palliative care can be defined as active and total care of the person whose illness no longer responds to curative treatment. This type of assistance will be the central point of our work, going through the vision of the patient, nurse and family in the process of finitude. Objectives: In this perspective, this investigation aims to disseminate the study on knowledge, meaning and deep symbols that people involved in this care go through and fragment problems that pass through. Methodology: This is an exploratory descriptive study of the bibliographic type. The survey of articles used took place in the month of May 2020, in the virtual health library, LILACS, MEDLINE and BDENF, aimed at evaluating deep meanings and symbols experienced by people who go through the process of this study. Conclusion: It was found by the work that the nursing professional is, in some cases, poorly prepared, poorly assisted or lacks support to provide better assistance to the family and their client. It is essential that patients and family members go through this moment together help each other, so that both are better prepared for the moment of death. It also showed the importance of spiritual / religious life and the opportune benefits they bring to their patients and family, being a great support for the passage through difficult times.